The prevalence of work stress among Royal Malaysian Police junior officers - Angamuthu, Prakash (2021)
The study aims to identify relationship between factor and potential causing the work stress among Royal Malaysian Police (RMP) Junior Officers. Further in this study investigate the contribution of working conditions, workplace relationships and workload factor which is known as primary work-related work stressors. Quantitative study was chosen to conduct at RMP and the population was from various departments at RMP headquarters. Data collection methods with the questionnaires are used as the survey instruments. Total of 301 questionnaires were send to various department in RMP. The result showed the workplace relationships are the significant and main factor of work stress which is in poor supervisory and unhelpful colleagues. Meanwhile for the working conditions and workload results showed non-significant relationship with work stress. This finding will helpful to the RMP to enhance the productivity of RMP junior police officers.